Kinetic control of solid state metathesis reactions - Martinolich, Andrew J., author; Neilson, James, advisor; Prieto, Amy, committee member; Krummel, Amber, committee member; Shores, Matthew, committee member; de la Venta, Jose, committee member (Colorado State University. Libraries, 2017)
The control of solid state reaction pathways will enable the design and discovery of new functional inorganic materials. A range of synthetic approaches have been used to shift solid state chemistry away from thermodynamic control, in which the most energetically favorable product forms, towards a regime of kinetic control, so that metastable materials can be controllably produced. This work focuses on the use of solid state metathesis in the preparation of transition metal sulfides and selenides, and understanding the reaction pathways through which these reactions proceed. Through a range of structural probes combined with thermal analysis techniques, the reaction pathways are identified. The challenge of changing the pathway is then tackled, aiming to maximize mixing in the reaction mixtures to overcome the classical diffusion limitations in solids at low temperatures. Changing the reaction pathway promotes the formation of metastable intermediates and products, highlighted by the formation of the superconducting cubic polymorph of CuSe2. Future work is suggested, surrounding the idea of maximizing diffusion and mixing at low temperatures. Understanding the properties of reactants, intermediates, and products to direct the reaction pathway is paramount in controlling the pathways through which reactions occur. This will progress the field of synthetic solid state chemistry towards the ability to design materials and reactions that are not limited by thermodynamics, in turn yielding the discovery of a range of new, functional compounds.